Cold-Water Corals and Other Vulnerable Biological Structures on a North Pacific Seamount After Half a Century of Fishing - Du Preez, Cherisse; Swan, Kelly D.; Curtis, Janelle M. R. (Frontiers in Marine Science, 2020)
Addressing growing threats of overexploitation to the world’s oceans is especially challenging in the High Seas, where limited data and international jurisdiction make it difficult to determine where and when conservation measures are necessary. Of particular concern are vulnerable marine ecosystems (VMEs)—special habitats on the seafloor that are highly sensitive to disturbance and slow to recover. To ensure the long-term conservation and sustainable use of marine resources, regional fisheries management organizations are committed to identifying the locations of VMEs and responding to prevent significant adverse impacts (SAIs). For over 50 years, Cobb Seamount—a shallow underwater volcanic mountain in the Northeast Pacific Ocean—has been commercially fished by multiple nations using various types of gear. Here we have assimilated data from fisheries records and a recent visual survey on the seamount. Our findings show a variety of habitat-forming emergent biological structures widely distributed on Cobb Seamount and generally depth-stratified into high-density assemblages (≥1 m-2). Our spatial analyses show that fishing has also been widely distributed, overlapping the habitat of the biological structures. We found fewer cold-water corals, sponges, and other biological structures in areas with higher recent fishing effort and documented evidence of fishing impacts, such as extensive mats of coral rubble and a high abundance of derelict fishing gear entangled with dead or damaged organisms. Based on the average density of “lost” gear (2,785±1,003 km-2), we can confidently estimate that hundreds of thousands of items of derelict fishing gear are currently entangled with the seafloor of Cobb Seamount and that these pose an ongoing threat to biological structures, the biogenic habitats they create, and the species they support. Such impacts can persist for decades or centuries to come. This study contributes and discusses new information on the condition and distribution of biological structures, VME indicator taxa, physically complex biogenic ecosystems, and human impacts on Cobb Seamount. These data will be necessary to identify the location(s) of potential VMEs and SAIs on this heavily fished seamount in the High Seas.